Biological Investigation of Jatropha gossypiifolia: A Stiff Medicinal Plant in Bangladesh: Biological Investigation of Jatropha gossypiifolia - Mahmodul Islam,; Ariful Islam,; Mohammad Salim Hossain, (Iranian Journal of Pharmaceutical Sciences, 2017)
This study describes a biological investigation of methanolic extract of Jatropha gossypiifolia, a plant belonging to the family Euphorbiaceae. The aim of this investigation is to expose the viable phytochemical constituents properly as their contribution towards the antioxidant, anthelmintic and membrane stabilizing activities. The anthelmintic test was conducted on earthworm Pheritima phosthuma using five unique concentrations of the extract and albendazole as standard drug. The extracts were used for the investigation of antioxidant activity followed by DPPH (Diphenylpicrylhydrazyl) assay and using BHT (tert-butyl-1-hydroxytoluene) as a standard. The crude methanolic stem and leaves extract of J. gossypiifolia (Jatropha gossypiifolia) was conducted to attempt for membrane stabilizing activities using standard protocols. The leaves and the stems portions considerably have the antioxidant property of 3.186 μg/ml and 10.56 μg/ml respectively. According to the absorbance values of the various extract solutions, results of the colorimetric analysis of total phenolic contents are that the leaves cover the highest Phenolic content (65.66mg/g in GAE (Galic Acid Equivalent)) rather than the stem portion (33.332mg/g in GAE). The leaves and stem methanolic extract was found both at hypotonic solution and heat induced conditions, inhibit 39.19±0.26%, 38.17±0.14 and 27.39±0.15%, 26.97±0.47% hemolysis of erythrocyte membrane respectively, when comparing with standard acetyl salicylic acid. The preliminary phytochemical evaluation of methanolic extract of J. gossypiifolia confirmed the presence of glycosides, tannins, phytosterols, triterpenoids, diterpenes, saponins and phenols both at its leaves and stem portions. The results of the study showed that the plant extract has potential membrane stabilizing, anthelmintic, antioxidant activities with significant phytochemicals.